Comparing outcomes of sheet grafting with 1:1 mesh grafting in patients with thermal burns: A randomized trial. Issue 2 (March 2015) - Nikkhah, Dariush; Booth, Simon; Tay, Sherilyn; Gilbert, Phillip; Dheansa, Baljit
Abstract Background In many units, the standard mesh ratio is 1.5:1, but in our unit we have a 1:1 mesher, which does not expand the skin but provides regular fenestrations. There is some evidence that the unexpanded 1.5:1 meshed graft compares favourably with sheet grafts from a cosmetic perspective whilst reducing the risk of graft failure secondary to a subgraft haematoma, but none comparing the 1:1 meshed graft with the sheet graft. We conducted a randomized trial to compare surgical outcomes in unfenestrated sheet grafts with 1:1 meshed grafts. Methods All patients aged ≥16 years undergoing skin grafts with either a sheet or a 1:1 mesh for burn reconstruction were included. Patients on steroids, those with conditions that impair healing, and burns >20% were excluded. Patients were randomized into the sheet grafting or mesh graft using a computer-generated allocation system. The mean percentage of graft loss was assessed by a Visitrak overlay system. At 3–4 months, 7–8 months and at 1 year, photos were taken for scar assessment using the Vancouver Scar Score (VSS). Results Out of 72 patients, 48 patients (24 sheet vs. 24 mesh) completed the trial at 12 months. The mean age was 58 years (range 21–90). There was no total loss of graft in either group. The mean percentage of graft loss due to haematoma formation was higher in the sheet graft group (10%) compared to the 1:1 mesh group (6%) (P < 0.062). The VSS score was 5 in both groups at 12 months. There was no significant difference in scar quality between the treatment groups. Conclusion These results show that the 1:1 mesh graft is superior to the sheet graft with regard to graft loss, although this result is not statistically significant. There are comparable findings in terms of cosmetic perspective at 12 months post-operatively in both arms of the trial.